2013
DOI: 10.1103/physrevb.87.075435
|View full text |Cite
|
Sign up to set email alerts
|

Band offsets and density of Ti3+states probed by x-ray photoemission on LaAlO3/SrTiO3

Abstract: A set of LaAlO3/SrT iO3 (LAO-STO) interfaces has been probed by x-ray photoemission spectroscopy in order to contrast and compare the effects of LAO overlayer thickness and of the growth conditions on the electronic properties of these heterostructures. These effects are tracked by considering the band-offset and the density of Ti +3 states, respectively. It is shown that the dominant effects on the local electronic properties are determined by the O2 partial pressure during the growth. In particular, a low P(… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
46
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 31 publications
13
46
0
Order By: Relevance
“…Furthermore, due to its large band gap (≈7.9 eV) [20], the CBM of GAO is above that of STO. Accordingly, in contrast to LAO/STO [15,28,30,40], the heterointerface between GAO and STO is found to be of type I.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Furthermore, due to its large band gap (≈7.9 eV) [20], the CBM of GAO is above that of STO. Accordingly, in contrast to LAO/STO [15,28,30,40], the heterointerface between GAO and STO is found to be of type I.…”
Section: Discussionmentioning
confidence: 79%
“…Similar observations have been made for other polar oxide heterostructures. In particular, the related heterostructure LAO/STO does not show a potential gradient as inferred from HAXPES [5,23,[27][28][29][30].…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…While agreeing in sign, the value obtained here is significantly higher than the offset reported by other photoemission studies of PLD-grown heterostructures. 10,21,35 Note that a possible small downward bending of the STO-VBM towards the interface would imply an even larger offset directly at the interface. In contrast, from photoemission on samples grown by molecular beam epitaxy (MBE), Segal et al have recently concluded on an offset value similar to ours, but of opposite sign, i.e., a type-I interface.…”
Section: Band Alignment At the Interfacementioning
confidence: 99%
“…This is probably the reason why this interesting phenomenon escaped the attention of previous investigations, 13,30 although some broadening of the Sr 3d has been reported occasionally. 31 We now turn to the two final and most intriguing open questions: which is the origin of the extra Sr-2 component and what determines the shift in BE? The extra Sr might well migrate from the bulk of SrTiO 3 that can be considered for our purposes as an infinite Sr reservoir.…”
mentioning
confidence: 99%